Designing sport and recreation programming: Towards enhancing consumers' participation in tourism industry - Lim, Khong Chiu (Universiti Utara Malaysia Press, 2007)
Programme planning and management are essential elements in assuring the success of leisure services for people of all ages and backgrounds.One of the hallmarks of good programming in sport and recreation is the extent to which how well an organization manages its resources and organizes activities to meet the wants and needs of different people and different groups.In this paper, I will examine the fundamental thrust of sport and recreation related to management planning by focusing on a related programming models.Thus, an approach to sport and recreational programming model adapted from the available literature will be emphasized.Apart from understanding the programming model, there is a need to better understand the application of marketing strategies for sport and recreation programmes that is provided by the tourism industry which can be regarded as triggers and anchors of the engagement process.The issues and challenges in programming sport and recreational activities will be outlined.Finally, the suggestions towards enhancing consumers' participation in sport and recreational activities in tourism industry will be discussed.